Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1103/physreva.90.031601
|View full text |Cite
|
Sign up to set email alerts
|

Spin-orbit coupling in periodically driven optical lattices

Abstract: We propose a method for the emulation of artificial spin-orbit coupling in a system of ultracold, neutral atoms trapped in a tight-binding lattice. This scheme does not involve near-resonant laser fields, avoiding the heating processes connected to the spontaneous emission of photons. In our case, the necessary spin-dependent tunnel matrix elements are generated by a rapid, spin-dependent, periodic force, which can be described in the framework of an effective, time-averaged Hamiltonian. An additional radio-fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
71
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 48 publications
(96 reference statements)
0
71
0
Order By: Relevance
“…The 3U triplon excitation is interesting in its own right and in connection with Efimov physics [50][51][52]. Our findings are also relevant in the context of driven experiments, e.g., for generating gauge fields [30][31][32] and spin-orbit interactions [33][34][35], where energy absorption at the driving frequency needs to be minimized. It would also be interesting to study the fine-structure changes in the spectral function induced by the higher bands of the optical lattice through effective multibody interactions [53][54][55] and renormalized hopping [56,57].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The 3U triplon excitation is interesting in its own right and in connection with Efimov physics [50][51][52]. Our findings are also relevant in the context of driven experiments, e.g., for generating gauge fields [30][31][32] and spin-orbit interactions [33][34][35], where energy absorption at the driving frequency needs to be minimized. It would also be interesting to study the fine-structure changes in the spectral function induced by the higher bands of the optical lattice through effective multibody interactions [53][54][55] and renormalized hopping [56,57].…”
Section: Discussionmentioning
confidence: 79%
“…They have been found in the spectral function at zero temperature using the variational cluster approach (VCA) [27,28] and strong-coupling calculations [26], and they are also reproduced in the current and kinetic energy susceptibilities calculated by DMRG [29]. The recently renewed interest in high-dimensional lattice bosons out-of-equilibrium to realize complex effective Hamiltonians including gauge fields [30][31][32] and spin-orbit interactions [33][34][35] by nonequilibrium driving, and the recent real-time generalization [36] of bosonic dynamical mean-field theory * hugo.strand@unifr.ch † philipp.werner@unifr.ch (BDMFT) [37][38][39][40][41], call for a systematic investigation of the positions, origins, and temperature behaviors of these high-energy fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…Although SOC with equal Rashba and Dresselhaus magnitudes have been proposed [28][29][30] and realized [31,32], to access more general forms of SOC, most proposals [33][34][35][36][37] and recent experimental work [38] focus on generating non-Abelian gauge fields, which can be considered as TR-breaking forms of SOC. There exist only a few proposals for specific forms of (TR-invariant) SOC [39,40] and, thus far, no experimental realization.…”
Section: Introductionmentioning
confidence: 99%
“…Our method relies on a combination of microwave (MW) drives to change the spin states and lattice shaking [29] to couple the spins with the atomic motion. If the optical lattice is inversion symmetric, the resulting SOC can be TR invariant.…”
Section: Introductionmentioning
confidence: 99%
“…A fascinating property of such system is that the effective flux in each plaquette is on the order of one flux quanta, large enough to reach the quantum Hall regime and enable the exploration of topological signatures [3][4][5][6][7][8][9][10]. Theoretical studies have also revealed various interaction effects in such system [12][13][14][15][16][17][18][19][20][21][22][23][24], and in particular, pointed out the possibilities of majorana fermions [20,22] and exotic spin textures [15,18].To date, most studies on the spin-orbit coupled atomic gases in optical lattices have concentrated on the lowest-band physics under various tight-binding approximations [12][13][14][15][16][17][18][19][20][21][22][23][24], while the high-band physics has been rarely explored. Moreover, even for the lowest band(s), it is questionable whether the conventional Wannier wavefunction without SOC can still be used to construct the tight-binding model, as the SOC can induce coupling between different bands and the original Wannier basis could be problematic.…”
mentioning
confidence: 99%